Do the American guideline-based leisure time physical activity levels for civilians benefit the mental health of military personnel? - Tsai, Kun-Zhe; Liu, Pang-Yen; Lin, Yen-Po; Chu, Chen-Chih; Huang, Wei-Chun; Sui, Xuemei; Lavie, Carl J.; Lin, Gen-Min (Frontiers in Psychiatry, 2023)
This study aimed to clarify the association of American guideline-based leisure time physical activity (PA) level with mental health in 4,080 military personnel in Taiwan. The moderate intensity PA level was assessed according to the total running time per week (wk) reported in a self-administered questionnaire over the past six months, and was categorized into PA level <150, 150-299, and ≥300 min/wk. Mental stress was assessed by the Brief Symptom Rating Scale (BSRS)-5 in which the point ≥15 was classified as great mental stress. Suicide ideation (SI) was graded as 1 for mild, 2 for moderate and 3 or 4 for severe. Multivariable logistic regression analysis was employed to determine the association between PA and mental health, while adjusting for demographics, smoking, alcohol intake, betel nut chewing and obesity. As compared to participants with PA levels <150 min/wk, those with PA levels 150-299 min/wk and ≥300 min/wk had less possibilities of SI ≥1 [odds ratios (ORs) and 95% confidence intervals (CIs): 0.58 (0.40-0.83) and 0.23 (0.14-0.36), respectively] and SI ≥1 and/or BSRS-5 ≥15 [ORs: 0.55 (0.39-0.79) and 0.21 (0.13-0.34), respectively]. The possibilities were more remarkably lower for SI ≥2 [ORs: 0.37 (0.20-0.68) and 0.10 (0.04-0.26), respectively] and SI ≥2 and/or BSRS-5 ≥15 [ORs: 0.35 (0.20-0.62) and 0.10 (0.04-0.25), respectively]. Our findings indicate that participating in moderate-intensity leisure time PA level ≥150 min/wk may have a positive effect on mental health among military personnel. The impact appears to be even more significant when engaging in a higher PA level ≥300 min/wk.